Correlations of noninvasive BOLD and TOLD MRI with pO2 and relevance to tumor radiation response. Issue 5 (27th June 2013) - Hallac, Rami R.; Zhou, Heling; Pidikiti, Rajesh; Song, Kwang; Stojadinovic, Strahinja; Zhao, Dawen; Solberg, Timothy; Peschke, Peter; Mason, Ralph P.
<x xml:space="preserve">Abstract</x> Purpose To examine the potential use of blood oxygenation level dependent (BOLD) and tissue oxygenation level dependent (TOLD) contrast MRI to assess tumor oxygenation and predict radiation response. Methods BOLD and TOLD MRI were performed on Dunning R3327‐AT1 rat prostate tumors during hyperoxic gas breathing challenge at 4.7 T. Animals were divided into two groups. In Group 1 (n = 9), subsequent 19F MRI based on spin lattice relaxation of hexafluorobenzene reporter molecule provided quantitative oximetry for comparison. For Group 2 rats (n = 13) growth delay following a single dose of 30 Gy was compared with preirradiation BOLD and TOLD assessments. Results Oxygen (100%O2) and carbogen (95%O2/5%CO2) challenge elicited similar BOLD, TOLD and pO2 responses. Strong correlations were observed between BOLD or <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg5f3fhsk7" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />R2*</alternatives> response and quantitative 19F pO2 measurements. TOLD response showed a general trend with weaker correlation. Irradiation caused a significant tumor growth delay and tumors with larger changes in TOLD and R1 values upon oxygen breathing exhibited significantly increased tumor growth delay. Conclusion These results provide further insight into the relationships between oxygen sensitive (BOLD/TOLD) MRI and tumor pO2. Moreover, a larger increase in R1 response to hyperoxic gas challenge coincided with greater tumor growth delay following irradiation. Magn Reson Med 71:1863–1873, 2014. © 2013 Wiley Periodicals, Inc.